A Meta Synthesis Study of Postgraduate Thesis using Lesson Study in Turkey - Akalın, Samet; Kılıç, Abdurrahman (Fırat University, 2022)
The study aims to explore the current status of the postgraduate thesis conducted in Turkey on the Lesson Study model, which is the concept of teachers' professional development. Theses related to the lesson study professional development model were searched using the keywords "lesson research" and "lesson study" in the database of “The Council of Higher Education National Thesis Center”. A total of 36 thesis studies were identified with the specified keywords. Out of 22 doctoral dissertations and 8 master thesis published between 2012-2020, which meet the research criteria, were included in the research. The results of the studies included in the research were analyzed by content analysis using the meta-synthesis technique. With meta-synthesis studies, the aim is to handle the studies in a specific field on a qualitative basis, and to present the similarities and differences comparatively. As a result of the analysis, four dimensions were revealed: the topics covered by the teachers at study meetings, difficulties faced in lesson study, the contributions of the lesson study and recommendations about the lesson study. The results of the study are thought to provide great convenience in terms of being a comprehensive resource for researchers who will work in the field of “lesson study”, which is a professional development model and for beginning a wider perspective for them.

Bu araştırmanın amacı, öğretmenlerin mesleki gelişim kavramı olan ders imecesi (Lesson Study) modeliyle ilgili Türkiye’de yapılan lisansüstü tez çalışmalarının mevcut durumunu çalışma sonuçlarından hareketle ortaya koymaktır. Ders imecesi mesleki gelişim modeli kapsamındaki lisansüstü tezler ‘‘ders imecesi’’, ‘‘ders araştırması’’ ve ‘‘lesson study’’ anahtar kelimeleri kullanılarak Yükseköğretim Kurulu Ulusal Tez Merkezi veri tabanında taranmıştır. Belirtilen anahtar kelimelerle toplam 36 lisansüstü tez çalışması tespit edilmiştir. Araştırma kriterlerini karşılayan, 2012-2020 yılları arasında yayınlanmış 22 doktora ve 8 yüksek lisans tez çalışması araştırma kapsamına alınmıştır. Araştırmaya dâhil edilen çalışmaların sonuçları meta sentez tekniği kullanılarak içerik analiziyle analiz edilmiştir. Meta-sentez çalışmaları aynı konuda yapılan nitel araştırmaların yine nitel bir anlayış doğrultusunda ele alınmasını, benzer ve farklı yönlerinin karşılaştırmalı olarak ortaya konmasını içermektedir. Yapılan analiz sonucunda, imece toplantılarında üzerinde konuşulan konular, ders imecesinde yaşanan zorluklar, ders imecesinin katkıları ve ders imecesine dair öneriler olmak üzere dört boyut ortaya çıkarılmıştır. Çalışma sonucunda ortaya çıkarılan bulguların bir mesleki gelişim modeli olan ders imecesi alanında çalışma yürütecek araştırmacılara kapsamlı bir kaynak olması ve geniş bir bakış açısı kazandırması bakımından büyük kolaylık sağlayacağı düşünülmektedir.
TÜRKİYEDE DERS İMECESİ MODELİ KULLANILARAK YAPILAN LİSANSÜSTÜ TEZLER ÜZERİNE BİR META SENTEZ ÇALIŞMASI